Importance of Picture Activity in Comprehensive Formation of Preschool Children - Ulugberdiyeva Dilbar Qarshibekovna (Zien Journals, 2023)
This article provides information about visual activity as the main means of providing aesthetic education to children.
Keywords: Drawing; making things from clay; application